The impact of internet use frequency on non-suicidal self injurious behavior and suicidal ideation among Chinese adolescents: an empirical study based on gender perspective - Xueyan Yang; Moye Xin; Kun Liu; Bilun Naz Böke (BMC, 2020)
Abstract Background We attempted to find if there were gender differences in Non-suicidal self injurious (NSSI) behaviors and Suicidal ideation among Chinese adolescents, then analyze the impact of Internet use frequency on these variables among adolescents of different genders. Methods Based on the data from 6 high-schools and 4 universities in 4 cities in China, the gender difference in NSSI behaviors and Suicidal ideation and their related factors were analyzed in the study. Results Gender differences were found during different purposes of Internet use; There was no significant gender difference in NSSI behaviors among Chinese adolescents, yet females reported significantly higher intensity of suicidal ideation compared to males; Internet use frequency could explain the prevalence of NSSI behaviors and Suicidal ideation by gender, to some categories. Conclusions There were gender differences in Internet use frequency among adolescents; Gender difference of NSSI engagement among Chinese adolescents was not statistically significant; Females had higher suicidal ideation than males; the overuse of social softwares was found to be a risk factor to both NSSI engagements and suicidal ideations for both genders; males would engage less NSSI behaviors when they spent more time on knowledge sharing softwares while might have more suicidal ideation when they spent too much time on gaming.